DAMPAK PENGGUNAAN ARTIFICIAL INTELLIGENCE PADA KEAMANAN SIBER: SEBUAH KAJIAN TERHADAP POTENSI KEUNTUNGAN DAN ANCAMAN - Rafika Widalala, Rasya; Novalina Khairunissa, Amanda; Ananda Dika, Juhar; Az Zahra Wijanarko, Allyssa (Berajah Journal, 2024)
Artificial Intelligence (AI) is now widely used in cybersecurity to detect threats while maximizing its benefits. The rapid transformation of technology makes cybersecurity a critical issue that needs to be anticipated in today's digital era. In this research, a comprehensive study is conducted on the impact of using AI in cybersecurity, especially on the potential benefits and threats that may arise. The purpose of this research is to explore the benefits resulting from the use of AI in detecting cyber threats and identify the most significant types of cyber attacks. The method used is Systematic Literature Review (SLR), by reviewing 39 papers published between 2020 and 2024. The originality of this research lies in the in-depth analysis of the potential benefits and risks of AI threats in cybersecurity. The results of this study confirm that AI can improve the efficiency and effectiveness of cyber threat detection. This research is expected to provide new insights into the dynamics of cybersecurity and open up opportunities for further research development.